Promotion and Price Analysis of Purchase Decisions Bear Brand Milk During The Covid-19 Pandemic at PT. Aneka Rasa Citra Sejati, Jakarta - Rajagukguk, Peter; Haryono, Bambang; Hardani, Hardani; Fadholi, Arief (International Journal of Social and Management Studies, 2021)
Promotion and price are important factors in realizing a company’s sales goals. Promotion is very influential on the company’s efforts to achieve maximum sales volume, as well as price perceptions will determine consumer behavior in deciding purchases. This research was conducted on customers of PT. Aneka Rasa Citra Sejati, Jakarta aims to analyze promotional factors and price perceptions that influence customer purchasing decisions for bear brand milk during the covid-19 pandemic. The sample in this study amounted to 105 respondents with a simple probability sampling method. The method used in data analysis is descriptive quantitative with correlation coefficient test, regression equation, F test, T test and Determination test, statistical data processing using SPSS 25 software. The results show that R square is 0.536 or 53.6%. This means that 53.6% of purchasing decisions are influenced by promotion and price factors. The correlation value between promotion and price on purchasing decisions is 0.732, which means there is a strong influence between variables X1, X2, and Y. Multiple linear regression coefficient test shows that Y= 1.723+0.395X1+0.354X2. The analysis above shows that sales promotion and price perception have a strong and significant influence on purchasing decisions, and the conclusion Ha is accepted that there is an influence of promotion and price on purchasing decisions of bear brand milk